Arterial Embolization in Large Uterine Fibroids : A 4-Year Single Center Experience: Uterine Fibroid Embolization - Çakır, Volkan; Ballı, Ömür (International Journal of Scientific Research and Management (IJSRM), 2019)
Purpose: Current knowledge concerning the use of uterine artery embolization (UAE) in large uterine fibroids is limited with the majority of studies being limited to case reports. The present retrospective study aimed to investigate the impact of UAE on symptoms and tumor size in symptomatic women with at least one large uterine fibroid.Methods: 39 patients undergoing UAE for symptomatic large uterine fibroids (>5cm) were consecutively enrolled in this study. All patients underwent a detailed physical examination and contrast-enhanced pelvic MRI at 3, 6 and 12 months after the procedure.Results: Compared to baseline values (7.8 ± 2.4 cm), the mean diameter of the fibroids significantly reduced at 3rd (5.5 ± 1.7 cm), 6th (4.2 ± 1.3 cm) and 12th (3.1 ± 0.6 cm) months follow-up (p50 % reduction in fibroid diameter was acquired in 87 % of the participants.Conclusion: Uterine artery embolization provides 60 % reduction in fibroid volume and a 92 % improvement in fibroid-related symptoms in patients with large fibroids at the end of 12 months follow-up.